2022
DOI: 10.1155/2022/9506328
|View full text |Cite|
|
Sign up to set email alerts
|

Scanning Imaging Study of Patients with Parkinson’s Disease Lower Urinary Tract Dysfunction Based on Linear Equation

Abstract: A predictive method based on a linear equation was proposed to study the factors influencing lower urinary tract dysfunction in Parkinson’s disease. A 10-month follow-up of 200 selected Parkinson’s patients from January to December 2020 used a linear regression equation to analyze whether depletion function was associated with a specific nonmotor function loss, and a linear regression equation was used for analysis. A loss of emptiness function was used to determine whether there are complications associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%